Enhancing land use classification with fusing dual-polarized TerraSAR-X and multispectral RapidEye data - Abdikan, Saygin; Bilgin, Gokhan; Sanli, Fusun Balik; Uslu, Erkan; Ustuner, Mustafa (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2015)
The contribution of dual-polarized synthetic aperture radar (SAR) to optical data for the accuracy of land use classification is investigated. For this purpose, different image fusion algorithms are implemented to achieve spatially improved images while preserving the spectral information. To compare the performance of the fusion techniques, both the microwave X-band dual-polarized TerraSAR-X data and the multispectral (MS) optical image RapidEye data are used. Our test site, Gediz Basin, covers both agricultural fields and artificial structures. Before the classification phase, four data fusion approaches: (1) adjustable SAR-MS fusion, (2) Ehlers fusion, (3) high-pass filtering, and (4) Bayesian data fusion are applied. The quality of the fused images was evaluated with statistical analyses. In this respect, several methods are performed for quality assessments. Then the classification performances of the fused images are also investigated using the support vector machines as a kernel-based method, the random forests as an ensemble learning method, the fundamental k-nearest neighbor, and the maximum likelihood classifier methods comparatively. Experiments provide promising results for the fusion of dual polarimetric SAR data and optical data in land use/cover mapping. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License. Distribution or reproduction of this work in whole or in part requires full attribution of the original publication, including its DOI.
Keywords: image fusion; TerraSAR-X image; RapidEye image; multispectral; synthetic aperture radar; classification; SUPPORT VECTOR MACHINES; MULTISENSOR IMAGE FUSION; COVER CLASSIFICATION; SAR; INTEGRATION; RADARSAT; Environmental Sciences & Ecology; Remote Sensing; Imaging Science & Photographic Technology